Stensö Castle 2015 - Rundkvist, Martin; Umeå University (Umeå University, 2016)
Investigations in 2015 in different parts of the archaeological site at Stensö Castle, Östra Husby parish, Östergötland, identified the western section of the castle's ringwall as well as a number of heaps of material which was extracted from the ruins for reuse. A rune carving was discovered on the outside of the southern tower, with the inscribed name 'Helge' - possibly a builder, worker, or the tower's architect. The excavations yielded rich finds of medieval ceramic, for the most part Early Red glazed ware (ca. 1250-1350 C.E.).

Purpose:

The aim of the archaeological investigations at Stensö Castle was to build upon the results from the 2014 excavation season at Stensö Castle.

The dataset consists of a series of images documenting excavations at Stensöborg, as well as an excel file describing these excavation images. The download package also contains the excavation report.

Arkeologiska undersökningar (2015) i Stensöborg, Östra Husby socken, Östergötland, identifierade västra delen av borgens ringmur, samt ett antal högar med byggnadsmaterial som brutits ur ruinerna för återanvändning. En runristning upptäcktes på det södra tornets utsida med namnet Helge - möjligen en byggnadsarbetare eller tornets arkitekt. Utgrävningarna gav rika fynd av medeltida keramik, mestadels äldre rödgods (ca. 1250-1350 e.K.).

Datasetet innehåller bilder tagna under arkeologiska undersökningen, samt en excel-fil som dokumenterar dessa bilder. Dataset-mappen innehåller även en utgrävningsrapport.
Stensöborg 2015
Excavations in 2015 at Stensö Castle
Keywords: Middle Ages; medeltid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi